YIELD AND QUALITY OF WINTER WHEAT DEPENDING ON THE MINERAL NUTRITION - Шакалій, С. М. (Scientific Progress & Innovations, 2013)
The investigation data of influence of different norms of mineral fertilizers on productivity and protein content in wheat grain mild winter are presented. It is established that the application of fertilizers has an impact on the increase of productivity of grain and contributes to an increase in protein content in grain. Using correlation analysis a close relationship between yield and protein content of winter wheat (r=0,80) is established. Winter wheat yield considerably changes from weather conditions during vegetation period and norms of mineral nutrition. The best results are for the full protection of plants + Basfoliar 36 Extra.